Comparison of dacron and nylon-flocked self-collected vaginal swabs and urine for the detection of Trichomonas vaginalis using analyte-specific reagents in a transcription-mediated amplification assay. Issue 3 (13th December 2011) - Jang, Dan; Gilchrist, Jodi; Portillo, Eder; Smieja, Marek; Toor, Ramandeep; Chernesky, Max
Abstract : Objectives: To compare self-collected vaginal swab (SCVS) types and first-catch urine (FCU) to diagnose Trichomonas vaginalis using analyte-specific reagents designed to be used in a transcription-mediated amplification assay. Methods: A total of 241 women (group A) collected a FCU and a SCVS using a dacron swab (APTIMA collection kit). A second group of 289 women (group B) collected two SCVS using one dacron swab and one nylon-flocked swab. Results: Of 75 young women (street youth) determined to be infected with T vaginalis only seven reported symptoms of vaginal discharge or irritation. Using a cutoff of 50 000 relative light units, the sensitivity and specificity was 97.2% and 97.6%, respectively for dacron SCVS compared with 41.7% and 100% for FCU in group A; 92.3% and 98.8% for dacron SCVS and 92.3% and 99.2% for flocked-nylon SCVS in group B. The assay tested 96 samples in 6 h. Conclusions: Dacron and nylon-flocked SCVS performed equally well and significantly better than FCU using analyte-specific reagents in the APTIMA transcription-mediated amplification assay. Either swab type could be used for self-collection.